Cardiac Rhabdomyoma in 9 Months Infant: From Echocardiography Perspective - Jordy Liong; Andi Alief Utama Armyn; Rheza Rivaldi Salam; Jauhar Mario; Herwin Irawan (International Medical Journal Corp. Ltd, 2025)
Background: The most prevalent benign cardiac tumor in neonates, cardiac rhabdomyoma, is frequently associated with tuberous sclerosis complex (TSC). Based on their dimensions and positioning, these tumors may result in obstructive cardiac lesions, arrhythmias, or hemodynamic instability. Echocardiography is the primary diagnostic instrument for detecting and monitoring cardiac rhabdomyomas, as well as for differentiating them from other intracardiac malignancies. Case Report : This case report describes a 9-month-old newborn diagnosed with cardiac rhabdomyoma, focusing on the echocardiographic findings, clinical presentation, and therapy strategy. Echocardiographic imaging identified many hyperechoic masses within the ventricles; further echocardiographic evaluations demonstrated spontaneous regression, thereby corroborating the diagnosis. Conclusion : The absence of genetic evidence between MRI and TSC hinders a definitive connection. This case underscores the importance of non-invasive imaging in guiding the diagnosis and treatment of pediatric cardiac cancers.